Perancangan Konten Sosial Media Untuk Meningkatkan Brand awareness Kamala Kopi - Sekar Lintang Rachmawati; Agus Priyadi; Candra Supriadi (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
The coffee industry in Indonesia is growing rapidly and encouraging coffee shops, including MSMEs, to strengthen their branding strategies through digital media. This study aims to design and evaluate Instagram social media content to increase brand awareness of Kamala Kopi, a local coffee shop in Gunungpati, Semarang. The method used is the Multimedia Development Life Cycle (MDLC) with stages of concept, design, material collection, assembly, testing, and distribution. The content produced consists of music videos, promotional posters, and menu visuals, which were then tested through internal and external validation, as well as a questionnaire administered to 68 respondents. The research results showed a positive and significant influence of Instagram content on brand awareness of 1.007 with a coefficient of determination of 90.4%. These findings confirm that content on Instagram social media plays an important role in strengthening the visibility of SME brands and can be an effective strategy to increase brand awareness.